Tumor-derived exosomal miRNA-141 promote angiogenesis and malignant progression of lung cancer by targeting growth arrest-specific homeobox gene (GAX). Issue 1 (1st January 2021) - Wang, Wulong; Hong, Guodai; Wang, Siyuan; Gao, Wenbin; Wang, Ping
ABSTRACT: Previous researches have suggested that exosomal miRNA-141 has association with metastatic lung cancer, however, its role and regulatory mechanism require further study. In this study, exosomes were isolated from lung cancer patients and normal human serum and identified. We found that the expression of miRNA-141 was up-regulated in the lung cancer serum exosomes compared with the normal serum exosomes. When the exosomes were extracted for co-culture with HUVECs, they were absorbed and distributed around the nucleus by confocal microscopy. Moreover, exosomal miRNA-141 from A549 significantly not only promoted the migration and invasion of A549 but also increased the cell proliferation, tube formation of HUVECs. In order to reveal the mechanism of exosomal miRNA-141, bioinformatics analysis revealed that miRNA-141 targeted the binding of Growth arrest-specific homeobox gene (GAX) in the 3ʹUTR region, and confirmed by MS2-RIP assay and dual-luciferase assay. Exosome miRNA-141 could down-regulate the expression of GAX. Taken together, our results demonstrate that tumor-derived exosomal miRNA-141 promote angiogenesis and malignant progression of lung cancer by targeting GAX. It provides a new possibility for the treatment of lung cancer. Graphical abstract: uf0001